Potential effect of opium addiction on lipid profile and blood glucose concentration in type 2 diabetic patients in Iran. (4th July 2019) - Hoseini, Somaye Sadat; Saadatjoo, Seyed Alireza; Nakhaee, Samaneh; Amirabadizadeh, Alireza; Rezaie, Maryam; Mehrpour, Omid
ABSTRACT: Background: Diabetes is one of the most common chronic diseases in the world. People believe that opium improves blood glucose and lipid profiles in these patients and controversial studies show the effect of consumption of opium in controlling these indices. Accordingly, this study aimed to compare the serum levels of blood indices such as fasting blood glucose (FBS), Hemoglobin A1c (HbA1c) and lipid profile in opium users and non-users in type ΙΙ diabetic patients. Methods: In this cross-sectional study, among type II diabetic patients referred to the Diabetes Clinic of Birjand 45 opium users and 135 non-users were selected and entered the study by the convenience sampling method. Results: The results of this study showed that the mean serum levels of FBS, HbA1c, and serum lipid profiles were not significantly different between the two groups of opium users and non-users, but the levels of triglyceride (TG) were significantly 0.18 unit higher in the opium users, compared to non-opium users. Conclusion: According to the results, the use of opium does not affect the indices of blood glucose, HbA1c and serum lipid profiles except triglyceride in diabetic patients. The general belief that opioid use reduces biochemical indices does not seem to be correct. Abbreviations: FBS: fasting blood sugar; HbA1c: Hemoglobin A1c; LDL: low-density lipoprotein; HDL: High-density lipoproteins; HDL-C: High-density lipoproteins-cholesterol; BMI: Body mass index; IQR: Inter quartile range; TG: triglyceride; TC: total cholesterol; NS: non-significant; S: significant; ATN: Acute tubular necrosis